Lightweight and integrity‐protecting oriented data aggregation scheme for wireless sensor networks. (1st March 2017) - Zhao, Xiaomin; Zhu, Jiabin; Liang, Xueli; Jiang, Shuangshuang; Chen, Qingzhang
Abstract : In recent years, some research used classical and heavyweight encryption technology to realise data privacy and integrity protection in data aggregation of wireless sensor networks. The challenge is the balance between resource constraints and the complexity of the deployment. In this study, the authors proposed a lightweight and integrity‐protecting oriented data aggregation scheme for wireless sensor networks (LIPDA) which has lightweight, secure and easy operability to preserve data privacy and integrity during data aggregation in wireless sensor network. First, a distance‐based formation scheme of network topology is presented to balance the energy consumption of cluster heads. Then, a structure of complex number, which composes from the private factor of the nodes and the original data, is composed. The complex number is encrypted by additive homomorphic encryption method, which can realise the data aggregation without any decryption. Also, the reliability of data is ensured by using integrity verification method based on the complex operation. The theoretical analysis and simulation results show that the proposed scheme LIPDA can meet the requirement of privacy protection. Moreover, compared with related work, LIPDA has lower calculation, less traffic, higher accuracy and verifiable completeness.